(untitled) (Third Sector Social Economic Review, 2026)
The rise of online news in the current century has led to fundamental changes in how information is created, disseminated, and consumed. Curatorial journalism, a human-centered practice involving the selection, editing, and presentation of news content in a form accessible to the target audience, has come to the fore. News curation has been presented as an antidote to the information overload ecosystem. The study examines the literature on journalism practices and roles, news curation and formats, digital intermediaries, and the structures of the journalism ecosystem. It addresses how many journalists are now considered information managers, what style curation products can adopt to attract audience interest, and the value proposition issue of curation products in an environment where trust is a concern. In the study, news agencies, newspapers, and thematic websites were examined using the keywords news curation, gatekeeping, digital intermediaries, and email news/newsletters, and the data was interpreted using thematic analysis methods. The study concluded that curators selected news stories presented in video, photo, and written formats, with summaries of the day’s most important news available through paid, free, SMS package, and WhatsApp subscriptions. This approach prioritized both increasing interest in the media and preventing readers from being exposed to excessive information overload. The study highlights the significant research potential in the field of media, yet reveals that despite the prominence of curatorial journalism in online news centers, there is a scarcity of academic literature examining its various aspects. It aims to contribute to future research efforts by addressing this gap.